Sex Differences in Cardiac Rehabilitation Outcomes - Smith, Joshua R; Thomas, Randal J; Bonikowske, Amanda R; Hammer, Shane M; Olson, Thomas P (Circulation research, 2022)
Cardiovascular disease is a leading cause of morbidity and mortality in males and females in the United States and globally. Cardiac rehabilitation (CR) is recommended by the American Heart Association/American College of Cardiology for secondary prevention for patients with cardiovascular disease. CR participation is associated with improved cardiovascular disease risk factor management, quality of life, and exercise capacity as well as reductions in hospital admissions and mortality. Despite these advantageous clinical outcomes, significant sex disparities exist in outpatient phase II CR programming. This article reviews sex differences that are present in the spectrum of care provided by outpatient phase II CR programming (ie, from referral to clinical management). We first review CR participation by detailing the sex disparities in the rates of CR referral, enrollment, and completion. In doing so, we discuss patient, health care provider, and social/environmental level barriers to CR participation with a particular emphasis on those barriers that majorly impact females. We also evaluate sex differences in the core components incorporated into CR programming (eg, patient assessment, exercise training, hypertension management). Next, we review strategies to mitigate these sex differences in CR participation with a focus on automatic CR referral, female-only CR programming, and hybrid CR. Finally, we outline knowledge gaps and areas of future research to minimize and prevent sex differences in CR programming.